Evaluation of Front Line Demonstration of Oilseeds in Raebareli District - Singh, K.K.; Singh, RPN; Mishra, Deepak (Indian Journal of Extension Education, 2020)
problem of low yield, Krishi Vigyan Kendra, Raebareli conducted front line demonstrations in the differentÂ localities of Raebareli District, Cultivation of high yielding varieties of oilseeds viz. Sesamum- (var. Tarun), Mustared- (var. CS-56 & Maya) yielded higher over local check. The cultivation practices considered underÂ Front Line Demonstration viz. use of improved varieties, proper seed rate, integrated pest management, irrigation and spraying of weedicide along with one hand weeding gave an average higher yield of 26.75 to 57.5 per cent in case of Sesamum (variety- Tarun) and 37.3 per cent for Mustard- variety- CS-56 , 54.29 per cent higher yield in case of Mustard variety Maya as compare to farmer’s practice. Yield of oilseed crops however, varied in different years which might be due to the other factors like soil moisture availability, climatic conditions, disease and pest attack as well as the change in the location of trails. The productivity gain under Front Line Demonstration over farmer’s practice created awareness and motivated the other farmers to adopt scientificÂ crop production and management.